Islamic Political Movement in Indonesia After “Aksi Bela Islam Jilid I, II and III" - Ahmad Sholikin (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2018)
Does “Aksi Bela Islam” show a new map of the Islamic Political Movement in Indonesia? Has the Movement for "Islamic Defense" changed the map of the Indonesian Islamist movement? What (or is there) a further impact on Indonesian democracy? Departing from these questions, this paper shows that, first, fragmentation of religious authority has occurred after the “Aksi Bela Islam”. NU and Muhammadiyah are no longer the sole authority in religious affairs in Indonesia. In addition to the fragmentation of religious authorities this article states that the ABI is a "protest movement" and "solidarity action" whose acceleration is stronger in the context of domestic issues, namely the Governor of Jakarta, which is vulnerable to maintaining long-term issues. So to be able to change the map of a strong Islamic political movement required a strong foundation of the initiators of the “Aksi Bela Islam”.